MODEL AUTOREGRESIF ANALISIS KAUSALITAS ANTARA JUMLAH UANG BEREDAR DAN TINGKAT PENDAPATAN NASIONAL: STUDI KASUS INDONESIA-THAILAND - Aliman Aliman (Journal of Indonesian Economy and Business (JIEB), 1998)
In his paper, Cheng Hsiao developed a statistical technique to developing Granger's testing of causality. A sequential method based Akaike's Final Prediction-Error criterion and Granger's concept of causality to multiple autoregressions is suggested. The method not only allows each variabel to enter the equation with a different time lag but also provides a reasonably powerful test of exogenety or causality. In latest development, the Hsiao method developed named Final Prediction-Error Criteria of Hsiao.In this paper, the Hsiao method is applied to Indonesian dan Thailand Money (M0, MI and M2) and nominal GDP (national income) data. It is found bivariante feedback model between M0, Ml and M2 with national income. Moreover, testing of causality in Indonesian and Thailand between M0 (money based) and national income finds strongly and certainly unidirectional causality from national income to M0. Ml and national income, in Indonesian and Thailand made a different result. In Indonesian, between Ml with national income finds unidirectional causality from national income to Ml (narrow money), while in Thailand, create unidirectional causality from Ml to national income. Between M2 and national income, also in Indonesian and Thailand made a different result. In Indonesian, between M2 with national finds unidirectional causality from M2 (broad money) to national income, while in Thailand, create unidirectional causality from national income to M2.